2021
DOI: 10.1371/journal.pone.0252126
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of hsa_circ_0001275 reverses dexamethasone-induced osteoblast growth inhibition via mediation of miR-377/CDKN1B axis

Abstract: Background Osteoporosis affects the quality of life among middle-aged and elderly individuals. In addition, dysfunction of osteoblasts can lead to the progression of osteoporosis. Circular (circ)RNAs are involved in various types of diseases, including osteoporosis. Moreover, it has been reported that hsa_circ_0001275 expression is upregulated in osteoporosis. However, the effects of hsa_circ_0001275 on the growth of osteoblasts remain unclear. Methods In the present study, the gene and protein expression le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…And the results further revealed that PTBP1 was able to bind to the mRNA of CDKN1B and improve its stability, resulting in the increased translation of CDKN1B protein. Mounting evidence suggested that CDKN1B is a key regulator of cell cycle progression, which was recognized as an important senescence marker in aging-related diseases such as osteoporosis [ 49 , 50 ], atherosclerosis [ 51 ] and Alzheimer’s disease [ 52 ]. In the present study, we performed functional experiments and reported that CDKN1B is positively correlated with chondrocyte senescence and OA progression.…”
Section: Discussionmentioning
confidence: 99%
“…And the results further revealed that PTBP1 was able to bind to the mRNA of CDKN1B and improve its stability, resulting in the increased translation of CDKN1B protein. Mounting evidence suggested that CDKN1B is a key regulator of cell cycle progression, which was recognized as an important senescence marker in aging-related diseases such as osteoporosis [ 49 , 50 ], atherosclerosis [ 51 ] and Alzheimer’s disease [ 52 ]. In the present study, we performed functional experiments and reported that CDKN1B is positively correlated with chondrocyte senescence and OA progression.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown a historical role of miRNA “sponging” in circRNA-miRNA–mRNA networks as playing important roles in both gene regulation and carcinogenesis [ 25 ]. For example, Xu et al recently showed that dexamethasone-induced osteoblast growth inhibition can be reversed by downregulating hsa_circ_0001275 which mediated the miR-377/CDKN1B axis in an effort to discover new treatment for osteoporosis [ 46 ]. Furthermore, Formosa et al previously demonstrated a role for miR-377 as a tumour suppressor miRNA targeting FZD4, a gene involved in epithelial-to-mesenchymal transition in prostate cancer [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Then, cells were treated with propanol (15 min), incubation solution (6 h), cobalt nitrate (15 min), and ammonium sulfide (5 min) (all 200 μL). Optical density at 490 nm was read on a microplate reader (Varioskan LUX; Thermo Fisher Scientific) [ 30 ].…”
Section: Methodsmentioning
confidence: 99%